2020
DOI: 10.21580/perj.2020.2.1.4883
|View full text |Cite
|
Sign up to set email alerts
|

Potensi Sekam Padi dan Jerami sebagai Alternatif Material Akustik

Abstract: <p class="Abstract">Technology that is increasingly developing produces equipments in the form of information, communication, production, transportation and entertainment facilities. Most of the equipments produce noises. Noise can be reduced by using acoustic dampers. This study aims to determine the potential for sound absorption from rice husks and straw as natural acoustic materials. Materials used include rice husks, rice straw, and resin. 12 cylindrical samples were made. Samples that have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…The sound absorption coefficient is influenced by the frequency of the sound source. The frequency is divided into three namely, the low-frequency value is less than 1000 Hz, the medium frequency value is between 1000 Hz to 4000 Hz, and the high-frequency value is more than 4000 Hz (Rohim et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sound absorption coefficient is influenced by the frequency of the sound source. The frequency is divided into three namely, the low-frequency value is less than 1000 Hz, the medium frequency value is between 1000 Hz to 4000 Hz, and the high-frequency value is more than 4000 Hz (Rohim et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Each composite has an optimum sound absorption capability at a certain frequency. The acoustic properties of the material as a sound absorber are very good at a frequency of 1000 Hz (Rohim et al, 2020). This is because at this frequency there is a waste of energy which increases the value of the sound absorption coefficient.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Di beberapa daerah di Jawa Tengah, Yogyakarta dan Jawa Timur, para petani memanfaatkan dan menyimpan jerami untuk pakan ternak, baik sapi maupun kerbau. Sebagian juga diolah untuk pupuk fermentasi, tetapi hal ini jarang sekali dilakukan di masa-masa sekarang [2] Sementara itu di negara maju, jerami telah dapat dimanfaatkan secara langsung sebagai bahan bangunan yang justru memberikan nilai tambah sesuai kondisi cuaca setempat, yaitu mampu menjadi insulator pada saat berlangsungnya musim dingin [3]. Menurut…”
Section: Pendahuluanunclassified
“…Rice straw fiber can also be used as a sound absorber [18]. Rice husk hasa sound absorption capacity of 0.034 dB, and straw has a sound absorption capacity of 0.030 dB [19]. Data obtained from acoustic studies showed that the highest value of sound absorption coefficient of 6400 Hz was noticed for composite specimens developed using rice husk and saw dust reinforced with hybridized polymer composites [20].…”
Section: Introductionmentioning
confidence: 99%